Tamaddun & sejarah : etnografi kekerasan di Aceh - Adan, Hasanuddin Yusuf, 1962- (Jogjakarta : Prismasophie Press, 2003)
Politics and violence in Nanggroe Aceh Darussalam Province
Includes bibliographical references and index
Keywords: Political violence -- Indonesia -- Aceh; Islam and politics -- Indonesia -- Aceh; Aceh (Indonesia) -- Politics and government